Wolbachia: endosymbiont of onchocercid nematodes and their vectors - Manoj, Ranju Ravindran Santhakumari (Parasit Vectors, 2021)
BACKGROUND: Wolbachia is an obligate intracellular maternally transmitted, gram-negative bacterium which forms a spectrum of endosymbiotic relationships from parasitism to obligatory mutualism in a wide range of arthropods and onchocercid nematodes, respectively. In arthropods Wolbachia produces reproductive manipulations such as male killing, feminization, parthenogenesis and cytoplasmic incompatibility for its propagation and provides an additional fitness benefit for the host to protect against pathogens, whilst in onchocercid nematodes, apart from the mutual metabolic dependence, this bacterium is involved in moulting, embryogenesis, growth and survival of the host. METHODS: This review details the molecular data of Wolbachia and its effect on host biology, immunity, ecology and evolution, reproduction, endosymbiont-based treatment and control strategies exploited for filariasis. Relevant peer-reviewed scientic papers available in various authenticated scientific data bases were considered while writing the review. CONCLUSIONS: The information presented provides an overview on Wolbachia biology and its use in the control and/or treatment of vectors, onchocercid nematodes and viral diseases of medical and veterinary importance. This offers the development of new approaches for the control of a variety of vector-borne diseases. GRAPHIC ABSTRACT: [Image: see text]